2023
DOI: 10.1002/bse.3451
|View full text |Cite
|
Sign up to set email alerts
|

Does resource bricolage foster SMEs' competitive advantage and financial performance? A resource‐based perspective

Abstract: Small and medium‐sized enterprises (SMEs) in emerging economies strive to achieve and sustain their financial and competitive positions in a dynamic resource‐constrained environment. The concept of resource bricolage has received little attention in the literature on emerging economies. To fill this gap, we draw perspectives from the resource‐based view to examine the impact of resource bricolage on the competitive advantage and financial performance of SMEs in Pakistan. We argue that organizational innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…• Unlike CB-SEM, PLS-SEM can reliably estimate parameters under non-normal data distributions (Hair et al, 2019) • This powerful component-based technique has been widely used in recent studies (e.g., Abid et al, 2023;Abualigah et al, 2022;Aftab, Sarwar, Kiran, Qureshi, et al, 2022;Aftab, Sarwar, Kiran, Abid, & Ahmad, 2022;Farrukh et al, 2022;Kim et al, 2019;Ojo et al, 2022;Ojo & Raman, 2019;Pham et al, 2020;Sarwar et al, 2023;Sharma et al, 2021;Shoaib et al, 2021).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Unlike CB-SEM, PLS-SEM can reliably estimate parameters under non-normal data distributions (Hair et al, 2019) • This powerful component-based technique has been widely used in recent studies (e.g., Abid et al, 2023;Abualigah et al, 2022;Aftab, Sarwar, Kiran, Qureshi, et al, 2022;Aftab, Sarwar, Kiran, Abid, & Ahmad, 2022;Farrukh et al, 2022;Kim et al, 2019;Ojo et al, 2022;Ojo & Raman, 2019;Pham et al, 2020;Sarwar et al, 2023;Sharma et al, 2021;Shoaib et al, 2021).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The use of PLS‐SEM may be rationalized for a variety of reasons: The PLS‐SEM technique enables scholars to simultaneously evaluate the relationships between items and their related latent constructs (e.g., measurement model) and the relationship between constructs (e.g., structural model). Hair et al (2017) confirmed its versatility for complex frameworks, specifically for models including moderation and mediation. PLS‐SEM is suitable for both small and large datasets and can provide accurate results. Unlike CB‐SEM, PLS‐SEM can reliably estimate parameters under non‐normal data distributions (Hair et al, 2019). Compared to other path modeling tools like LISREL or AMOS, variance‐based [SmartPLS] provides a simple graphical interface. This powerful component‐based technique has been widely used in recent studies (e.g., Abid et al, 2023; Abualigah et al, 2022; Aftab, Sarwar, Kiran, Qureshi, et al, 2022; Aftab, Sarwar, Kiran, Abid, & Ahmad, 2022; Farrukh et al, 2022; Kim et al, 2019; Ojo et al, 2022; Ojo & Raman, 2019; Pham et al, 2020; Sarwar et al, 2023; Sharma et al, 2021; Shoaib et al, 2021). There are two phases to the analysis process in PLS‐SEM: (1) the external model and (2) the internal model, discussed in the following sections.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Furthermore, PLS-SEM is regarded as superior in assessing mediation compared to regression (Preacher & Hayes, 2004). Moreover, PLS-SEM is a choice of many recent studies (e.g., Abid et al, 2023;El-Garaihy et al, 2022;Feng et al, 2022;Luo et al, 2022;Sarwar et al, 2023;Singh et al, 2022) due to its reliable and consistent estimations. For these reasons, PLS-SEM is a good choice for this empirical study.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In addition, the DCT approach urges companies to exploit their possible opportunities to achieve a competitive advantage and outperform their rivals (Teece, 2014). Earlier evidence indicates that the effective use of dynamic capabilities fosters firm outcomes (Hernández-Linares et al, 2021) through the development of eco-friendly practices (Aftab, Abid, Sarwar, & Veneziani, 2022) and the efficient handling of ecological challenges (Abid et al, 2023). Additionally, since the nature of sustainable environmental practices is non-static , a company may build its own necessary "green knowledge" through green…”
Section: Stakeholder Theory and Dynamic Capabilities Theorymentioning
confidence: 99%
See 1 more Smart Citation